Проект адміністративно-побутового корпусу яхт-клубу у м. Дніпро - Врадій, Артем Олександрович; Vradii, Artem (My University, 2024)
Розроблено проект адміністративно-побутового корпусу яхт-клубу у місті Дніпро. Генеральний план комплексу відповідає чинним нормам містобудування та враховує специфіку розташування і призначення будівлі. Архітектурно-планувальне рішення та конструктивна схема 9-поверхової будівлі розроблені з урахуванням її функціонального призначення, технологічних, санітарно-гігієнічних, протипожежних та інших нормативних вимог. На підставі інженерно-геологічних вишукувань та розрахунків навантажень запроектовано пальовий фундамент. Розроблено будівельний генеральний план на період зведення корпусу. Проект комплексно розв'язує питання архітектурного планування, конструктивного вирішення та організації будівництва адміністративно-побутового корпусу яхт-клубу. A project for the administrative and amenity building of a yacht club in the city of Dnipro has been developed. The general plan of the complex complies with the current urban planning standards and takes into account the specifics of the location and purpose of the building. The architectural and planning solution and structural design of the 9-storey building were developed taking into account its functional purpose, technological, sanitary, fire safety and other regulatory requirements. Based on engineering and geological surveys and load calculations, a pile foundation was designed. A construction master plan for the period of construction of the building was developed. The project comprehensively addresses the issues of architectural planning, constructive solution and organisation of the construction of the administrative and amenity building of the yacht club.
Project of the administrative and amenity building of a yacht club in Dnipro
Keywords: яхт-клуб; адміністративно-побутовий корпус; пальовий фундамент; yacht club; administrative and amenity building; pile foundation